PERANCANGAN GAME EDUKASI PENGENALAN KOMPONEN ELEKTRONIKA MENGGUNAKAN ADOBE FLASH ( STUDI KASUS DI KELAS X TEKNIK AUDIO VIDEO SMK N 2 PATI) - Suwadi Suwadi; Mars Caroline Wibowo (Pixel :Jurnal Ilmiah Komputer Grafis, 2018)
The author designed the application "Electronic component recognition game" as a learning media or educational game for class X students majoring in Audio Video Engineering SMK N 2 Pati. The author chooses Grade X Audio Video Engineering students as the target user because it considers theoretically the initial difficulty of the students of Audio Video Engineering about the understanding of electronic components specifically and the learning methods that are still practically conventional. With educational games, it is expected to create an interactive and fun learning process that is expected to overcome existing problems.This application will provide an understanding of the initial introduction of electronic component materials simply and easily. Through the introduction of electronic component games can be the beginning to create interactive educational games for students to give and build positive imagination to students and teachers. This application is designed by considering graphic concepts, education game criteria and user requirements. This research was implemented using the Action script programming language and Adobe Flash CS3 software. This application is very interactive and can be used as a teaching aid in learning electronic component materials at school or independently by the user. This application can also be improved to improve the quality of the application in the future.